2017
DOI: 10.1016/j.abb.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel starch branching enzyme from the picoalgae Ostreococcus tauri

Abstract: Starch branching enzyme is a highly conserved protein from plants to algae. This enzyme participates in starch granule assembly by the addition of α-1,6-glucan branches to the α-1,4-polyglucans. This modification determines the structure of amylopectin thus arranging the final composition of the starch granule. Herein, we describe the function of the Ot01g03030 gene from the picoalgae Ostreococcus tauri. Although in silico analysis suggested that this gene codes for a starch debranching enzyme, our biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 89 publications
(115 reference statements)
0
7
0
Order By: Relevance
“…Recombinant protein SBE1 enzymatic activity assay was detected according to previous research ( 32 , 33 ). Briefly, 10 μL recombinant protein was incubated with different concentrations of amylose (10 to 1,500 μg/mL) in 180 μL 50 mM NaCl in PBS buffer (pH = 7.0) at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant protein SBE1 enzymatic activity assay was detected according to previous research ( 32 , 33 ). Briefly, 10 μL recombinant protein was incubated with different concentrations of amylose (10 to 1,500 μg/mL) in 180 μL 50 mM NaCl in PBS buffer (pH = 7.0) at 37°C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…These two enzymes are suggestive of the presence of a α-1,4-glucan in the exometabolome of Micromonas . Members of the green algal lineage, like their true plant relatives, carry genes for carbon storage as starch, consisting of α-1,4-glucan units as amylose and amylopectin [ 58 , 59 ]. In PUL5, enriched genes included an N -acetylglucosamine kinase.…”
Section: Resultsmentioning
confidence: 99%
“…Other aminoacids that are well conserved are Glu399 (Glu526 in OsttaISA1) and Asp471 (Asp597 on OsttaISA1) Table 1. Numerous studies analyzing the role of these amino acids in the GH13 proteins showed that Asp363 acts as a catalytic nucleophile and would form a covalent intermediate by binding to the glucose moiety at the reducing end of the molecule, while Glu399 is the catalytic acid/base that would protonate the oxygen from the -1 glucose [29,51,58]. These aminoacids are involved in the so-called double displacement mechanism, which is proposed for all the reactions involving GH13 enzymes [59].…”
Section: Sequence Alignment and Phylogenetic Analysis Of Osttaisa1mentioning
confidence: 99%
“…Fig. (3A) shows in magenta the position of this putative CBM from OsttaISA1, and it can be clearly observed that it comprises six ß-strands forming the classical CBM ß-sandwich folding [27,29]. The central part of the protein is composed of the Catalytic Domain (CD), which is also conserved among the α-amylase family, and belongs to the family 13 of glycoside hydrolase from the CAZY database [51,61].…”
Section: Homology Modeling Of Osttaisa1mentioning
confidence: 99%
See 1 more Smart Citation